THE EFFECTIVENESS OF SOFTBALL OVERHAND THROW SKILL TRAINING MODEL ON BASIC THROWING SKILLS IN BLACK DIAMON CIREBON SOFTBALL PLAYERS - Elian, Septo (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The purpose of this study was to produce and test a softball overhand throw skill training model. The research method uses research and development methods adopted from the theory of Borg & Gall. There are ten steps used in this study, namely needs analysis, initial product development, expert evaluation, small group trials, product revisions, large group trials, product revisions, effectiveness tests, revisions, and the final product. The research subjects were u-17 novice athletes with a total of 15 subjects in small group trials, large group trials of 40 novice athletes and 40 subject effectiveness tests conducted on u-17 novice athletes at the Black Diamon Club Cirebon. The data analysis technique used in this study to test the effectiveness of the model is the normality test, homogeneity test and independent sample-test. The results of the research produced a product in the form of softball overhand throw skill training. For the 17 year old group, 24 training models have been validated and revised by experts. The implication of this study is that the training model is feasible and effective for use by the age of 17 and over in improving softball overhand throw skills.